Um estudo sobre a alfabetização para as pessoas em espaços de restrição e privação de liberdade por meio dos projetos de alfabetização no estado do Amazonas - Monteiro, Gabriela dos Santos (Brasil, 2025)
The research analyzes the pedagogical practices provided for in the Literacy Projects for people in spaces of restriction and deprivation of freedom in prison units in Manaus – AM. We start with the central question: What are the pedagogical practices foreseen in literacy projects for people in Spaces of Restriction and Deprivation of Freedom (ERPL) in prison units in Amazonas? As well as the following guiding questions: How are Projects organized for the literacy process of people in Spaces of Restriction and Deprivation of Freedom in Manaus? How are literacy courses offered to people in Spaces of Restriction and Deprivation of Freedom in the city of Manaus? To this end, the following specific objectives were established: elucidate concepts and theoretical perspectives regarding literacy for young people and adults in Spaces of Restriction and Deprivation of Freedom; identify the ways of organizing Projects for the Literacy process; verify the provision of literacy courses for people in spaces of restriction and deprivation of freedom through literacy projects. The methodology applied consisted of qualitative research with a documentary approach. The main authors used were: Onofre (2007,2014), Julião (2012,2017) and Freire (1982, 1983, 1994, 1997, 2024). Through the results, in the Writing My Future Project, the way educational actions were implemented were traditional, through studies based on a book, dividing the teachings into chapters. On the other hand, the practices foreseen and found in the First Letters Project, initially were the planning of content and the sequence of activities, aligned with the proposal offered, we were able to verify the educational actions described in the document in a didactic way, such activities were foreseen, the diagnosis initial session to assess the level of each participant, the literacy games and the conversation circle, these activities contribute significantly to student learning.